The Effect of Social Presence in Live Streaming Shopping on Tiktok Platform Users on Impulse Buying Behavior - Qierana Maulidya Fara; Arif Hartono (UNIVED Press, 2024)
Social presence is a theory that explains self-involvement in social interactions. Even though it is often not realized, social presence has an important role in explaining a person's condition towards the nature of virtual interaction. The flexibility of social presence makes this theory often applied in various scientific fields such as education, tourism, marketing to other fields, especially in the current digitalization era. One of the aims of this research is to explore and reaffirm the performance of social presence within the scope of live streaming marketing by involving consumer trust as a driver of impulsive buying behavior. This study adopts the SOR theory which explains the function of stimulus, organism, and response in influencing consumer behavior. This study has five variables, namely live streaming social presence, viewer social presence, broadcaster social presence, consumer trust, and impulse buying. This research was conducted using a quantitative approach with a convenience sampling technique and collected data from 188 respondents which were processed using SPSS and PLS-SEM. The main findings of this study indicate that the social presence of live streaming and social presence of watching has a positive and significant effect on consumer trust. Furthermore, consumer confidence has a positive and significant effect on impulsive purchases. In addition, the effect of social media presence on consumer trust is negative and insignificant.